« C’est dangereux, la formation ! » Entretien avec Françoise F. Laot, socio-historienne de l’éducation et de la formation des adultes - Aurélie Gonnet; Emmanuel Quenson (La Nouvelle Revue du Travail)
In this interview, Françoise F. Laot, a socio-historian of adult education and training, revisits her research on vocational training institutions. Highlighting the difficulties faced by women in being recognised as a training audience in their own right, she shows that training was essentially conceived and designed by and for men, who were often already qualified and working in large companies. Questioning the effects of the recent promotion of the figure of the individual as a free and responsible actor in his or her own development, she points out that the rejection of alternatives to individualisation has been a feature of the continuing vocational training system since its foundation. Lastly, this interview sheds light on the way in which the priority given to the logic of professionalisation and certification has led to the exclusion of activities (socio-cultural activities, activism) from the status of training, despite the fact that they contain just as much potential for learning and a much more collective approach.